Laparoscopy vs. Laparotomy for the Management of Abdominal Trauma: A Systematic Review and Meta-Analysis - Wang, Jianjun; Cheng, Liangwang; Liu, Jing; Zhang, Binyin; Wang, Weijun; Zhu, Wenxin; Guo, Yan; Bao, Chuanfei; Hu, Yunli; Qi, Shanxin; Wang, Kai; Zhao, Shuguang (Frontiers in Surgery, 2022)
Abstract Background There is still no consensus regarding the role of laparoscopy in trauma cases. The purpose of this paper is to assess the value of diagnostic and therapeutic laparoscopy for patients with blunt or penetrating abdominal trauma by performing a systematic review and meta-analysis. Methods PubMed, Embase, and the Cochrane library were systemically searched for the randomized controlled trials (RCTs) and non-RCT comparative studies on effectiveness and safety of laparoscopy versus laparotomy for the two authors independently performed the search, data extraction, and quality assessment. Results A total of 5,517 patients were enrolled in 23 eligible studies that were published in English. Meta-analysis results suggest that there is no significant difference in the incidence of missed injury and mortality between abdominal trauma patients receiving laparoscopy and those receiving laparotomy. Concerning postoperative complications, compared with patients in the open surgery group, those in the laparoscopy group are at a similar risk of intra-abdominal abscesses, thromboembolism, and ileus, while there is a decreased incidence of wound infection and pneumonia. Besides, subjects in the laparoscopy group experience shorter hospitalisation times and procedure times. For most outcomes, the sensitivity analysis yielded similar results to the primary analysis. Conclusion Laparoscopic surgery is a practical alternative to laparotomy for appropriate patients. The decision to perform laparoscopy should be based on the experience of the surgeon and the resources available.